2017
DOI: 10.1038/s41598-017-09825-7
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is a significant risk factor for the development of liver cirrhosis in chronic hepatitis C patients

Abstract: We explored the association between diabetes mellitus (DM) and the risk of hepatitis C virus (HCV)-related liver cirrhosis in Chinese patients with chronic hepatitis C (CHC). To examine the link between DM and liver cirrhosis, we conducted a case-control study of 210 Chinese CHC patients diagnosed with liver cirrhosis, comparing them to an age- and sex-matched control group of 431 CHC patients without liver cirrhosis. We conducted logistic regression analyses adjusting for demographic features and liver cirrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
(34 reference statements)
1
16
0
Order By: Relevance
“…Multiple large meta-analyses have shown that chronic HCV infection is associated with an increased risk of T2DM [7,8]. There is strong evidence that T2DM in the context of HCV infection results in increased risk of adverse liver outcomes, such as advanced fibrosis, decompensated cirrhosis and HCC [15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple large meta-analyses have shown that chronic HCV infection is associated with an increased risk of T2DM [7,8]. There is strong evidence that T2DM in the context of HCV infection results in increased risk of adverse liver outcomes, such as advanced fibrosis, decompensated cirrhosis and HCC [15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…4 HCV-associated T2DM has been shown to accelerate the clinical course of chronic HCV infection, significantly increasing the risk of fibrosis and its progression to cirrhosis, decompensation and HCC [15][16][17][18][19][20][21][22][23][24]. Multiple studies have shown a link between T2DM and the development of liver fibrosis.…”
Section: What Is the Clinical Relevance Of T2dm In Patients With Chromentioning
confidence: 99%
“…113 HCV infection alters many aspects of the relationship between the liver function and lipoprotein homeostasis, including by impairing the VLDL-releasing pathway, which is one of the causal mechanisms of hepatic lipid accumulation, dyslipidaemia and hypobetalipoproteinaemia. 9 The HCV core and non-structure 5A proteins interact with apolipoprotein (apo)A, 114 apoAII 115 and apoE, 116,117 and so might play roles in liver steatosis, mediated by the derangement of lipid metabolism. The HCV lipo-viral particles contain increased levels of apoC-III that may inhibit the activity of lipoprotein lipase, disturbing the intravascular catabolism of TG-rich lipoproteins.…”
Section: Chroni C Hepatitis Vir Al Infec Ti On and Lipid Profile Smentioning
confidence: 99%
“…In addition, interactions among hepatitis viruses, the host and the environment affect the progression of liver diseases. Considering the host‐related factors, metabolic syndrome (MetS) and associated diseases, such as obesity and insulin resistance/type 2 diabetes mellitus (T2DM), detrimentally affect the course of the disease, especially by accelerating liver fibrosis progression …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation